Assessing Burnout in Subgroups of Athletes Based on Gratitude and Perceived Coach-Athlete Relationship. Issue 2 (April 2022) - Yukhymenko-Lescroart, Mariya A.; Ruser, Jeffrey B.; Gabana, Nicole T.; Gilbert, Jenelle N.
The purpose of this study was to examine distinct groups of athletes based on their gratitude and coach-athlete relationships (CAR) and to compare the groups on three dimensions of athlete burnout: sense of reduced accomplishment, emotional and physical exhaustion, and sport devaluation. Types of gratitude measured included general trait gratitude, general state gratitude, and sport state gratitude. Cluster analysis with 576 intercollegiate athletes showed four distinct groups: "ungrateful in life and sport, and disconnected from the coach" (Group 1), "highly grateful in life and sport, and well-connected with the coach" (Group 2), "generally less grateful in life, but connected with the coach" (Group 3), and "generally grateful in life, but disconnected from the coach" (Group 4). Group 1 reported the highest levels of burnout. In contrast, Group 2 reported the lowest levels of burnout. Athletes in Groups 3 and 4 (which were similar on sport state gratitude, but differed on other indicators) reported moderate levels of burnout, but Group 4 athletes were more burned out than Group 3 athletes. Specifically, both groups reported similar levels of devaluation; yet, Group 4 scored higher on reduced sense of accomplishment and emotional/physical exhaustion than Group 3. Examination of group composition revealed that male athletes were overrepresented in Group 2 and underrepresented in Group 4, and Group 1 athletes tended to identify as non-religious. Taken together, findings point to the protective role that gratitude and a positive CAR may play in athlete burnout prevention.